A framework for designing, implementing, communicating and researching peer assessment. Issue 3 (16th April 2018) - Adachi, Chie; Tai, Joanna; Dawson, Phillip
ABSTRACT: The term 'peer assessment' may apply to a range of student activities. This imprecision may impact on the uptake of peer assessment pedagogies. To better describe peer assessment approaches, typologies of peer assessment diversity were previously derived from the education literature. However, these typologies have not yet been tested with 'real-life' peer assessment examples, nor do they consider broader contextual matters. We present an augmented peer assessment framework, refined through analysing faculty accounts of their peer assessment practices. Our framework subsumes previous attempts to classify peer assessment, and extends them to include technology use, resources and policy, which were new features of our data not present in previous frameworks. In the current higher education climate, these considerations may be crucial for the scalability and success of peer assessment. The framework proposed in this paper provides both precision and concision for researchers and educators in studying and implementing peer assessment.